2004
DOI: 10.1159/000080063
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c<i>-myc</i> mRNA in Hepatocellular Carcinomas, Noncancerous Livers, and Normal Livers

Abstract: Objectives: c-myc is a transcription factor that regulates cell proliferation, differentiation, and apoptosis. However, little is known about the clinical importance of c-myc mRNA expression in a primary hepatocellular carcinoma (HCC). In this study, we investigated whether a correlation existed between the level of c-myc mRNA expression and the occurrence of apoptosis or proliferative activity in an HCC. Methods: The levels of c-myc mRNA expression were quantified by real-time reverse transcriptase polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…A study on hepatocellular carcinoma demonstrated suppression of Cmyc mRNA in cancerous tissues than non-cancerous liver tissues [28]. Further, a significant positive correlation was observed between the levels of C-myc mRNA and occurrence of apoptosis [28]. Contrary to our findings, Johnson et al [29] showed that chemotherapy-treated cell lines with C-myc gene amplification survived significantly shorter time than patients without C-myc gene amplification.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…A study on hepatocellular carcinoma demonstrated suppression of Cmyc mRNA in cancerous tissues than non-cancerous liver tissues [28]. Further, a significant positive correlation was observed between the levels of C-myc mRNA and occurrence of apoptosis [28]. Contrary to our findings, Johnson et al [29] showed that chemotherapy-treated cell lines with C-myc gene amplification survived significantly shorter time than patients without C-myc gene amplification.…”
Section: Discussioncontrasting
confidence: 88%
“…In breast cancer, Lockett et al have noted high (100%) positivity of C-myc mRNA in stage I patients than in stage IIIB patients (50%) [11]. A study on hepatocellular carcinoma demonstrated suppression of Cmyc mRNA in cancerous tissues than non-cancerous liver tissues [28]. Further, a significant positive correlation was observed between the levels of C-myc mRNA and occurrence of apoptosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that a complex regulation pattern after HDAC inhibition mediates apoptosis via upregulation of c-myc, which has been found to be suppressed in hepatoma cells. 41,42 This complex regulation pattern in hepatoma cells is currently addressed in a separate study.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical data revealed overexpression of c‐myc in HCC, consistent with altered function of tumor hepatocytes (11). This may play a role in tumor development and/or progression (9), as it targets several genes that are negative regulators of cell cycle progression, such as p21 and p27, and thus is strongly implicated in control of cellular proliferation, apoptosis and differentiation (12).…”
mentioning
confidence: 99%